(untitled) (Libellarium: journal for research in the field of information and related sciences, 2021)
The paper deals with the possibilities of engaged interdisciplinary activity implemented at the crossroads of librarianship and contemporary art practices. By relying on the theoretical concepts on which critical librarianship is based on the one hand, and contemporary art on the other hand, a possibility is shown of their interference with the aim to introduce a critical perspective within librarianship through art and to establish a new methodology at the crossroads of the two disciplines. The aforementioned is demonstrated in the paper through the coexistence and activity of S. S. Kranjčević Library and Prozori Gallery (Zagreb City Libraries), the programmatic and curatorial concept of which deals with the questions of the manner in which the theoretical positions of contemporary art and their practical and discursive analysis can contribute to the visibility, importance, and cultural capital of the library, the library profession, and the encouragement of critical attitude within the framework of information and communication sciences, the branch of which being librarianship, with emphasis on the project Uncertain Interventions: LGBTIQ Users in Public Libraries as a case study. Finally, the paper introduces the concept of libraries as agonistic public spaces.